CD36 upregulates DEK transcription and promotes cell migration and invasion via GSK-3β/β-catenin-mediated epithelial-to-mesenchymal transition in gastric cancer - Wang, Jin (Aging (Albany NY), 2020)
Evidence indicates that the lipid scavenger receptor CD36 has pro-metastatic functions in several cancers. Although CD36 expression correlates with an unfavorable prognosis in gastric cancer (GC), its specific contribution to disease onset, progression, and/or metastasis remains unclear. Using bioinformatics analyses, we ascertained that CD36 expression was increased in metastatic GC specimens in The Cancer Genome Atlas and Gene Expression Omnibus databases and correlated with poor prognosis. In addition, higher CD36 expression was associated with lymph node metastasis (p < 0.05) and poor prognosis (p = 0.030) in 79 Chinese GC patients. Basal CD36 expression levels correlated positively with migration, invasion, and expression of epithelial-to-mesenchymal transition (EMT) markers in GC cell lines, a relationship confirmed by knockdown and overexpression experiments. Importantly, analysis of gene expression changes in CD36-knockdown GC cells led us to identify the chromatin-associated protein DEK as a c-Myc target that mediates activation of the GSK-3β/β-catenin signaling pathway to trigger EMT. These findings further our understanding of the mechanisms governing metastatic dissemination of GC cells and suggest the therapeutic potential of strategies targeting CD36.